Research on optimisation of rural tourism development path in Henan province - Dou Yingying; Dzhylkychieva Zhyldyz; Liang Zongzheng; Zhang Shuolei; Liang Liuke (Glasnik Srpskog Geografskog Društva)
Rural tourism, as an area of the tourism industry, demonstrates a steady growth trend, highlighting the importance of implementing measures to optimise it for the economic and socio-cultural prosperity of the regions. The purpose of the study is to develop recommendations for optimising and strengthening the promotion of rural tourism in Henan Province, which will contribute to the sustainable development of the region, the preservation of its cultural and natural legacy, and improving the living standards of the local population. The following methods were used: descriptive, deductive, generalisation and comparative analysis. The results of the study determined that Henan Province, with its rich cultural legacy, historical monuments, and nature, has essential prerequisites for the development of rural tourism. The analysis of the current state of this tourism industry in the region has identified the main problems and barriers faced by rural tourism in the process of its improvement. Therewith, it was established that investment difficulties, uneven infrastructure development, lack of qualified personnel in the field of tourism and the lack of effective programmes limit the potential of rural tourism in this region. Strategic recommendations include fostering local investments, implementing digital marketing strategies, and initiating community education programs in tourism basics. Special attention needs to be paid to optimising approaches to the development of this area at the local level to form a productive regional strategy in the field of tourism, which will contribute to economic growth, create new jobs, form appropriate marketing strategies for promoting tourism products, support environmental initiatives, use digital technologies and improve the well-being of the province in general. The practical importance lies in the possibility of using the results of the study by researchers who study the basics of rural tourism development and specialists in the tourism industry.